Pengembangan Instrumen Tracer Study Berbasis Cluster Sebagai Kontrol Mutu Lulusan Perguruan Tinggi - Muhamad Fakhrur Saifudin; Meita fitrianawati (UHN IGB Sugriwa Denpasar, 2021)
The purpose of this research is to develop a cluster-based tracer study instrument that can be used to measure the absorption rate of graduates based on competency. This type of research is development. This study uses the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation) i. The product appraisal instrument uses a quality assessment sheet involving material experts and an evaluation sheet which is used to determine the responses of stakeholders and graduates regarding the use of the product being developed. The type of data obtained is data about the process of developing a cluster-based tracer study instrument from the input of experts and graduates. The data analysis of this research used process data analysis and product quality data analysis. The results of the study were based on a feasibility test based on the material validator, assessment, and language validator which were assigned to the graduate assessment instrument with the criteria of